Development of ECDIS application for INDERA radar - Sianipar, R.; Sediono, Wahju (2009)
Electronic Chart Display and Information System ECDIS) is a computerized navigation system integrating variety of charts and navigation-related information that replaces the usage of paper chart. Nowadays, ECDIS usage is getting more recognized as being used for both navigation and collision avoidance task. The combination of ECDIS and radar allows the navigator to have an integrated navigation and tactical display to avoid both navigation hazards and interfering contacts. ECDIS uses the Electronic Navigation Chart (ENC) which contains all the chart information necessary for a safe navigation. This paper outlines how the ENC chart can be displayed with a well-known SevenC's ECDIS kernel software.